Cu‐Based Nanoparticles as Emerging Environmental Catalysts. Issue 2 (17th August 2018) - Deka, Pangkita; Borah, Biraj Jyoti; Saikia, Himadri; Bharali, Pankaj
Abstract: This account provides an overview of current research activities on nanoparticles containing the earth‐abundant and inexpensive element copper (Cu) and Cu‐based nanoparticles, especially in the field of environmental catalysis. The different synthetic strategies with possible modification of the chemical/ physical properties of these nanoparticles using such strategies and/or conditions to improve catalytic activity are presented. The design and development of support and/or bimetallic systems (e. g., alloys, intermetallic, etc.) are also included. Herein, we report synthetic approaches of Cu and Cu‐based nanoparticles (monometallic copper, bimetallic copper and copper (II) oxide nanoparticles/nanostructures) and impregnation of such nanoparticles onto support material (e. g., Co3 O4 nanostructure), along with their applications as environmental catalyst for various oxidation and reduction reactions. Finally, this account provides necessary advances and perspectives of Cu‐based nanoparticles in the environmental catalysis. Abstract : Cu‐based nanoparticles catalyze diverse chemical reactions of industrial importance. Cu as metallic, bimetallic and oxide nanoparticles are highlighted with their extensive applications in the field of environmental remediation/ treatments with especial emphasis on reduction and oxidation reactions. There are further opportunities in the field of Cu‐based electrocatalysts for fuel cell reactions.